THE EFFECT OF GOOD CORPORATE GOVERNANCE, THE ROLE OF INTERNAL CONTROL, AND COMPENSATION SUITABILITY ON FRAUD PREVENTION - I Ketut Edy Sukadiputra; Henny Triyana Hasibuan (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Good Corporate Governance, Internal Control, Compensation Suitability, Fraud Prevention. The frequent fraud cases occurring in village credit institutions (LPD)  have resulted in a decline in public trust in LPD. The implementation of good corporate governance and internal control is a strategic step that LPD can implement to improve the quality of management and supervision. Furthermore, compensation alignment is also a factor that can prevent fraud in LPD. The purpose of this study was to determine the effect of good corporate governance, internal control, and appropriate compensation on fraud prevention. This study was conducted in ten LPDs with the largest assets in Bali. The sample size was 57 respondents, using a purposive sampling technique. The collected data were then analyzed using multiple linear regression analysis. The results showed that good corporate governance, internal control, and appropriate compensation have a positive effect on fraud prevention. The implication of this study is that the implementation of GCG, an effective internal control system, and compensation alignment can reduce the risk of fraud.